ANALISIS KEPUASAN PELANGGAN PADA RESTORAN SOP TUNJANG PERTAMA (M1) DI PEKANBARU - Juang Novrianto (UIR Press, 2016)
Sop Tunjang Pertama (M1) Restaurants consist of 3 culinary spot that specialized in beef-basedsoup in Pekanbaru. The group is operated by family-based business system. The aim of thisstudy is to analyze customers’ perception of culinary service quality on the restaurants.Population are customers of Sop Tunjang Pertama (M1) Pekanbaru. The sample numberconsist of 145 customers who were distributed proportionally in Pinang branch, Kayu Manisbranch and Soekarno-Hatta branch. Variables are culinary service quality on the restaurantsthat consist of 5 dimensions are: tangible, reliability, responsiveness, assurance and emphaty.Data analyzed by using Importance Performance Analysis (IPA). The study reveals thataveragely the culinary service quality is aleady satisfied in 4 dimension that are: assurance(80%), emphaty (70%), responsiveness (69%) and reliability (66%), unless for tangible aspectthat is still less satisfied (58%). The culinary service quality that are need to be enhanced are:parking area, restaurant decoration, dining area comfortness and tidiness, peak hous servicepunctuality, readable and attractiveness of menu.